Visitors Perception about the Entertainment Parks in Dhaka City of Bangladesh (Global Journal of Management and Business Research, 2019)
Nowadays, entertainment parks are one of the paramount segments of the tourism industry of any country. Bangladesh is also a country with a full of attractive places for the visitors and tourists. Some of the entertainment parks are also made by the private sector entrepreneurs in Bangladesh. Due to rapid growth of urbanization, people are divested of enjoying natural attractive places, due to their time constraints. Therefore, the concept of entertainment park is becoming vital in developing countries like Bangladesh. Along with natural tourist spots, there are four main private sector entertainment parks that are located in Dhaka and Chittagong, the main cities of Bangladesh. They are: Fantasy kingdom, Nandan Park, Sishu Park, and FoyezLake. The tourism sector's contribution to the economy is also increasing day by day. In 2017, it was 4.2 percent of the GDP, increasing to 4.4 percent in 2018 1 1 knoema.com/atlas/Bangladesh/topics/Tourism/Travel-and-Tourism-Total-Contribution-to-GDP/Contribution-of-travel-and-tourism-to-GDPpercent-of-GDP . To develop this sector, a diversified approach with the concentration on theme-based entertainment parks might be more attractive to the urban people of Bangladesh. A large number of visitors desire entertainment parks, especially in Dhaka city. But the parks are extremely inadequate in numbers and also not in good condition. Hence, this study identifies the visitors' perceptions about the entertainment parks located in Dhaka city -the capital city of Bangladesh. This study was conducted among the visitors who have already visited the entertainment parks of Dhaka city. To conduct this study, a total of 214visitors were interviewed with the help of a structured questionnaire. Both descriptive and inferential statistics were used to analyze the data. Multivariate analysis techniques like factor analysis were performed to identify the factors related to the entertainment parks of Dhaka city. Multiple regression analysis was performed to identify the relationships between the factors and the overall conditions of the entertainment parks of Dhaka city. Results show that there are twelve factors which are important to the people of Dhaka city who frequently visit entertainment parks. The factors are: medical and first aid services, rides price and mobile network, road transport and discount facilities, trees and gardens, park employee's behavior & sitting facilities, food and toilet facilities, picnic spot facilities, drinking water facilities, attractiveness of the park, quiet and noiseless, open for all ages of people, and availability of the rides. It is suggested that the park authority should focus on the mentioned factors so as to make the entertainment parks more attractive to the increased number of visitors from Dhaka city.
Keywords: entertainment park; rides price; park employees behavior; quiet and noiseless; availability of rides